Pengaruh Budaya Organisasi dan Komitmen Organisasi Terhadap Organizational Citizenship Behaviour dengan Dukungan Organisasi Sebagai Variabel Mediasi pada Karyawan PT. Famili Raya Padang - Hariyono, Ridho; Putra, Ramdani Bayu; Dewi, Rindy Citra; Fitri, Hasmaynelis (Yayasan Kawanad, 2022)
This study aims to determine the relationship between Organizational Culture and Organizational Commitment to organizational citizenship behavior through organizational support as a moderating variable. This research was conducted at PT. Famili Raya Padang data were collected through questionnaires distributed to 80 respondents. Data testing techniques in this study include validity tests, reliability tests with Alpha Cronbach, Inner Model and analysis: (1) Organizational Culture has a positive and significant effect on Organizational Support with a significant level of 0.039 <0.05. (2) Organizational Commitment has a positive and insignificant effect on Organizational Support with a significant level of 0.792 > 0.05. (3) Organizational Culture has a positive and significant effect on Organizational Citizenship Behavior with a significant level of 0.045 <0.05. (4) Organizational Commitment has a positive and significant effect on Organizational Citizenship Behavior with a significant level of 0.044 <0.05. (5) Organizational support has a positive and insignificant effect on Organizational Citizenship Behavior with a significant level of 0.716 <0.05. (6) Organizational support cannot mediate the influence of Organizational Culture on Organizational Citizenship Behavior with a significant level of 0.631 < 0.05. (7) Organizational support cannot mediate the effect of Organizational Commitment on Organizational Citizenship Behavior with a significant level of 0.921 < 0.05.